Aspects of leaf anatomy of kudzu (Pueraria lobata, Leguminosae-Faboideae) related to water and energy balance - Netto, Adaucto Bellarmino de Pereira; Gabriele, Antonio Carlos; Pinto, Hilton Silveira (Pesquisa Agropecuaria Brasileira, 1999)
Kudzu is a cover crop that has escaped cultivation in some subtropical and warm temperate regions. Kudzu has previously demonstrated broad intraspecific physiological plasticity while colonizing new environments. The objective of this paper was to investigate characteristics of kudzu leaflet anatomy that might contribute to its successful growth in climatically distinct environments, and to escape cultivation as well. Fresh and fixed leaflet strips of field-grown plants were analyzed. The lower epidermis of kudzu showed a higher frequency of stomata (147 ± 19 stomata mm-2) than the upper epidermis (26 ± 17 stomata mm-2). The average number of trichomes per square milimeter was 8 for both the upper and the lower epidermis. The average trichome length was 410 ± 200 mm for the upper epidermis and 460 ± 190 mm for the lower epidermis. Cuticle thickness was not considerably different between lower and upper epidermis. The leaflet blade consisted basically of two layers (upper and lower) of unicellular epidermis, two layers of palisade parenchyma and one layer of spongy parenchyma. One layer of paraveinal mesophyll was found between palisade and spongy parenchyma. In conclusion, leaflets of kudzu present anatomical characteristics that might contribute to the broad physiological plasticity shown by kudzu.